Structure-activity relationship study of homoallylamines and related derivatives acting as antifungal agents - Suvire, Fernando Daniel (2006)
The synthesis, in vitro evaluation, and structure-activity relationship studies of homoallylamines and related derivatives acting as antifungal agents are reported. Among them, compounds N-(4-bromophenyl)-N-(2-furylmethyl)amine and N-(4-chlorophenyl)-N-(2-furylmethyl)amine reported here exhibited remarkable antifungal activity against dermatophytes. Theoretical calculations allow us to determine the minimal structural requirements to produce the antifungal response and can provide a guide for the design of compounds with these properties.